PRESEPSI GURU TENTANG KINERJA ADMINISTRASI SEKOLAH DI MTsN 2 SOLOK - Lathifah, Najmi Diyana; Sabri, Ahmad; Hasnawati, Hasnawati (UIN Imam Bonjol Padang, 2023)
Najmi Diyana Lathifah, with thesis title: